Combination Gel Formulation Extracts of Moringa Leaf and Red Betel Leaf as an Inhibitor of Acne-Causing Bacteria (Propionibacterium acne and Staphylococcus aureus) - Eko Sri Wahyuningsih; Wahono Sumaryono; Chaidir Chaidir (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
The most common skin disorder is acne (Acne vulgaris) which is a chronic inflammatory disease that occurs in the pilosebaceous unit. Infection can be caused by Propionibacterium acnes and Staphylococcus aureus. Moringa leaves are known to inhibit acne growth. Piper crocatum leaves are also thought to have antibacterial activity. The study aims to determine the effect of the combination of the two extracts in inhibiting the growth of acne-causing bacteria, also tested the gel formula to meet physical and chemical parameters as well as stability to temperature and storage, also to test the acute dermal irritation against rabbit. Each extract with a concentration of 0.3%; 0.6%; 1.25%; 2.5%; 5%; 10%; 20%, incubated then measured the inhibition zone, then determined the minimum inhibition zone concentration of the two extracts to determine the lowest levels of the extracts which still gave antibacterial activity against the tested bacteria by the well diffusion method. The extract combination was formulated in a gel preparation with the excipients Carbopol 940, PG, Phenoxyethanol, TEA, CMC, and Aquadest. Antibacterial activity test for gel preparations used the well method with positive control Medi-Klin® gel. Then the formula evaluation includes physical, chemical, and microbiological evaluations. The results showed that the combination gel form had activity against P. acne and S. aureus at concentrations of 2.5% : 2.5%. The combination gel preparation of the two extracts also has synergistic effect in inhibiting acne bacteria. The formula can meet physical and chemical parameters and is stable to temperature and storage.